Psikologi Kepemimpinan Pendidikan : Gaya, Pemberdayaan, dan Kinerja Organisasi - Rika Fadilatul Laila; Zahra Khoirun Nisa; Sinta Bela; Putri Aisyah; Zenol Rosul; Muallimin Muallimin (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2025)
This study explores leadership psychology within the context of education, focusing on the relationship between leadership styles, psychological empowerment, and organizational performance. Using a literature review method, the findings reveal that leadership styles such as transformational, democratic, and situational have a significant impact on creating a supportive and collaborative work environment. Effective leadership fosters psychological empowerment by enhancing employees' sense of meaning, competence, self-determination, and influence. This, in turn, directly contributes to increased motivation, job satisfaction, and overall performance within educational institutions. Therefore, a psychological approach to leadership is a crucial element in building competitive and adaptable educational organizations.